Anti-glycation properties of the aqueous extract solutions of dried algae products and effect of lactic acid fermentation on the properties. (1st February 2016) - Kuda, Takashi; Eda, Mika; Kataoka, Manami; Nemoto, Maki; Kawahara, Miho; Oshio, Satoshi; Takahashi, Hajime; Kimura, Bon
Highlights: Aqueous extract solutions (AESs) of 11 dried algae products were prepared. Ecklonia kurome showed high antioxidant and anti-glycation capacities. Anti-glycation in a BSA-methylglyoxal model agreed with DPPH radical scavenging findings. Results of a BSA-fructose model agreed those of O2 −1 radical scavenging. Lactobacillus plantarum AN6 increased the inhibitory effect of some AESs. Abstract: The antioxidant and anti-glycation properties in aqueous extract solutions (AESs) of 11 dried algae products were investigated. AESs of brown algae Ecklonia kurome (kurome) and Ecklonia stolonifera (tsuruarame) showed a strong DPPH radical-scavenging capacity and Fe-reducing power with high total phenolic compound content. On the other hand, superoxide anion radical-scavenging capacities of Porphyra sp. (iwanori, red alga), sporophyll of Undaria pinnatifida (mekabu, brown alga), and Gelidiaceae sp. (tengusa, red alga) were also high. Anti-glycation activities in BSA-fructose and BSA-methylglyoxal glycation were also high in kurome, while iwanori showed high activity. Results of the BSA-fructose model agreed with those of superoxide anion radical-scavenging. On the other hand, those of the BSA-methylglyoxal model agreed with those of the phenolic content, DPPH radical-scavenging capacity, and Fe-reducing power. Anti-glycation activities of iwanori, U. pinnatifida (wakame), and mekabu in the BSA-fructose model were clearly increased by fermentation with Lactobacillus plantarum AN6.